(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Patients’ rights are integral to human rights, encompassing autonomy, privacy and dignified treatment. These rights are vital for vulnerable individuals within society and are essential for ethical healthcare practices. This study aims to explore the knowledge of patient rights among hospitalized patients and those attending Outpatient Departments (OPDs). Materials and methods: A descriptive cross-sectional study was conducted during the period of June 2024 to September 2024 on 1000 hospitalized adult patients of Chattagram Maa-O-Shishu Hospital Medical College to find out the knowledge regarding patients’ rights. 1000 respondents were selected by using convenience sampling technique. A pretested questionnaire was used and data analyzed by SPSS v.22. Results: The survey showed most respondents were married (60%) and lived in urban areas (68%). Awareness of the Patient Rights Charter was high (70%), mainly via the internet. While 88% knew the right to choose a doctor and 93% valued compassionate care, only 60% felt hospitals upheld rights, citing negligence concerns. Conclusion: The survey reveals strong awareness of patients’ rights, yet only 60% feel these are upheld in hospitals due to privacy concerns linked to negligence. Improved communication and practices are needed to better protect and maintain patients’ rights in healthcare. JCMCTA 2025 ; 36 (1) : 51-55